Sequential MR imaging (with diffusion-weighted imaging) changes in metronidazole-induced encephalopathy - Rupinder Singh; Ramanjeet Kaur; Pawan Pokhariyal; Rajul Aggarwal (Indian Journal of Radiology and Imaging, 2017)
Metronidazole-induced neuro-toxicity, though rare, is known. A characteristic spatial distribution of lesions in cerebellar dentate nuclei and dorsal pons is known. However, temporal progression of lesions on magnetic resonance imaging (MRI) has not been described previously. We describe two such cases which presented initially with splenial hyperintesity and showed progression to characterstic lesions. Both cases improved with stoppage of metronidazole.